Modernism and the narrative of nation in jfk - Robert Burgoyne (Ilha do Desterro)
The debate over Oliver Stone’s JFK has been framed to date largely within the discourse of historiography, with greatest attention being paid to issues concerning the limits of fact and fiction, and the erosion of the presumed boundry between documentary and imaginative reconstruction.2 Defenders of the film have usually argued from a deeply theoretical position, pointing out the permeable nature of the border between factual discourse and imaginative reconstruction, as well as the protean quality of even the most substantial documentary record of the past.3 In this essay, I wish to shift the angle of approach to the film in order to consider another set of questions, revolving chiefly around the tension between the film’s formal innovations and its explicit aim to articulate a narrative of national cohesion. The film’s fragmentary form, I argue, can be revealingly seen as an expression of a national narrative in disorder and disarray, its collage-like narrative structure reflecting the disruption of the evolutionary or historical narrative that gives continuity to national identity.